Initiating change in highland Ethiopia : the causes and consequences of cultural transformation - Freeman, Dena (Cambridge University Press, 2002)
"In a rural community in southern Ethiopia, there are two types of rituals performed by the same people. Historical evidence suggests that one has shown remarkable stability over the years, while the other has undergone massive transformations. External factors are the same, so how is this to be explained? Dena Freeman focuses on new ethnographical and historical data from the Gamo Highlands of southern Ethiopia to tackle the question of cultural change and transformation. She uses a comparative perspective and contrasts the continuity in sacrificial rituals with the rapid divergence and differentiation in initiations.